Resting-State Functional Connectivity Signatures of Apathy in Community-Living Older Adults - Jang, Jung Yun; Han, S. Duke; Yew, Belinda; Blanken, Anna E.; Dutt, Shubir; Li, Yanrong; Ho, Jean K.; Gaubert, Aimée; Nation, Daniel A. (Frontiers in Aging Neuroscience, 2021)
Apathy predicts poor outcomes in older adults, and its underlying neural mechanism needs further investigation. We examined the association between symptoms of apathy and functional connectivity (FC) in older adults without stroke or dementia. Participants included 48 individuals (mean age = 70.90) living independently in the community, who underwent resting-state fMRI and completed the Apathy Evaluation Scale (AES). Seed-to-voxel analysis (cluster-level p-FDR < .05, voxel threshold p < .001) tested the association between AES scores and the whole-brain FC of brain regions involved in reward- and salience-related processing. We found that AES scores were negatively associated with FC of the right insula cortex and right anterior temporal regions (124 voxels, t = -5.10) and FC of the left orbitofrontal cortex and anterior cingulate regions (160 voxels, t = -5.45), and were positively associated with FC of the left orbitofrontal cortex and left lateral prefrontal (282 voxels, t = 4.99) and anterior prefrontal (123 voxels, t = 4.52) regions. These findings suggest that apathy in older adults may reflect disruptions in neural connectivity involved in reward- and salience-related processing.